Caesarean section scar causes myometrial hypertrophy with subsequent heavy menstrual flow and dysmenorrhoea. (October 2017) - Ewies, Ayman A.A.; Zanetto, Ulises
Abstract: In the recent years, maternity statistics world-wide show a continuous rise in the rate of Caesarean Section (CS) operation. Many CS deliveries are conducted despite having no clear obstetric indications. The CS scar is assumed to be related to many adverse clinical gynaecological symptoms such as intermenstrual bleeding, dysmenorrhoea, dyspareunia and chronic pelvic pain; however, the mechanism of this relation is not clear. Further, little is known about the effects of CS scar on uterine wall morphology, function or patho-physiology. We hypothesize that: (i) the CS scar causes myometrial hypertrophy (myohypertrophy) of the anterior uterine wall above the scar, and (ii) the scar-induced morphological changes in the uterine wall causes adverse clinical gynaecological symptoms such as intermenstrual bleeding, dysmenorrhoea, dyspareunia and chronic pelvic pain. This article discusses the hypothesis and its clinical implications, as well as presents supportive preliminary data and the emerging research to prove it.